Peer assessment that works - McDonald, Betty (Rowman & Littlefield, 2016)
Easy-to-digest, down-to-earth practical strategies for doing peer assessment without the normal challenges that face educators. Building trust and creating buy-in are essential to the success of peer assessment. Teacher moderation to ensure learning outcomes match is a central theme of the book. Cross checking for inconsistencies is underscored. Finally the interconnectedness of the roles of facilitator, student and significant others in the peer assessment process is emphasized.